2018
DOI: 10.3390/f9050258
|View full text |Cite
|
Sign up to set email alerts
|

Black Plastic Mulch or Herbicide to Accelerate Bur Oak, Black Walnut, and White Pine Growth in Agricultural Riparian Buffers?

Abstract: Abstract:This study was conducted in a riparian buffer bordering a 1 km segment of a headwater stream crossing a pasture site located in southern Québec (Canada). Three species were planted (black walnut (Juglans nigra L.), bur oak (Quercus macrocarpa Michx.), and eastern white pine (Pinus strobus L.)) with three vegetation treatments (control, herbicide (one application/year for 3 years), and black plastic mulch)). The main objective was to determine to which extent herbicide and plastic mulch, used with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Such soil conditions are beneficial to the studied hardwoods [51,57], despite that red oak, black walnut and hickories have a slight preference for NH 4 uptake [84][85][86]. Being highly sensitive to grass competitors, the studied hardwoods [50,59,87,88] may also benefit from the reduction in herbaceous plant cover following understory colonization by Rubus species [81].…”
Section: The Effect Of Shelterwood Characteristics On Underplanted Trmentioning
confidence: 99%
“…Such soil conditions are beneficial to the studied hardwoods [51,57], despite that red oak, black walnut and hickories have a slight preference for NH 4 uptake [84][85][86]. Being highly sensitive to grass competitors, the studied hardwoods [50,59,87,88] may also benefit from the reduction in herbaceous plant cover following understory colonization by Rubus species [81].…”
Section: The Effect Of Shelterwood Characteristics On Underplanted Trmentioning
confidence: 99%
“…Pesticide use in Brazilian crops has increased in the last two decades (Almeida et al 2017) due to the emergence of resistant weeds (Cerdeira et al 2011). However, herbicides are used in some contexts as a restoration tool to control weed competition, and their effect on the trees is species‐dependent (Ortega & Pearson 2010; Truax et al 2018). Griscom et al (2009) observed that herbicide application, although effectively removing competitive grass, also killed trees and shrub sprouts.…”
Section: Introductionmentioning
confidence: 99%